Human Epidermal Growth Factor Receptor 2 [HER‐2/neu] Amplification and Microsatellite Stable Status in Gastric and Gastroesophageal Adenocarcinoma: Assessing Frequency and Prognostic Implications at the Cancer Institute of Iran - Samaneh Salarvand; Abbas Mohammadi; Reza Shahsiah; Farzaneh Bagheri; Mahsa Gholizadeh; Somayeh Jolany‐Vangah; Ebrahim Esmati; Marzieh Lashkari; Vahid Soleymani; Seraj Zareh‐Dehabadi; Vahid Mehrtash; Amirmohsen Jalaeefar; et al. (Cancer Reports)
ABSTRACT Background Molecular targeted therapy and immunotherapy have shown promise in managing gastric adenocarcinoma. The amplified expression of Human epidermal growth factor receptor‐2 (HER‐2) and microsatellite stable (MSI) status serve as indicators of response to targeted therapy and immunotherapy, respectively. Aims This study assessed the frequency of MSI status and HER‐2 expression in a pretreated sample of Iranian patients with gastric and gastroesophageal (GE) adenocarcinoma. Methods and Results We conducted HER‐2/neu expression and mismatch repair (MMR) system analyses on specimens from patients with gastric and GE adenocarcinoma at the Cancer Institute of Iran. Archival tissues from 135 mainly pre‐treated surgical specimens of gastric adenocarcinoma cases were used for HER‐2 analysis, and 66 specimens were used for MSI analysis. All specimens were tested for HER‐2 amplification, revealing that 11 patients (8.1%) had HER‐2 amplification, and three out of 66 examined patients exhibited MSI‐H. Patients with HER‐2 overexpressed specimens had a shorter median overall survival (OS) compared with HER‐2 negative cases (21 months (95% CI: 1.4–40.6) vs. 31 months (95% CI: 22.9–39), p = 0.18). The median disease‐free survival (DFS) for HER‐2 positive and negative patients was 15 and 28 months, respectively (p = 0.25). The estimated median OS and DFS for patients with negative MSI were 26 and 20 months, respectively. However, none of the patients with MSI‐positive status experienced recurrence, metastases, or death within the follow‐up period; thus, MSI‐H patients had a significantly improved OS and DFS (p = 0.018 and 0.020). Conclusion HER‐2 expression, while less common in our Iranian population compared with North American or Western European countries, showed a nonsignificant trend toward poor outcomes in patients with gastric adenocarcinoma. MSI‐H status was highly infrequent in our population, suggesting that immunotherapy may not be a beneficial treatment for a significant fraction of Iranian patients with gastric adenocarcinoma. However, a minority may still benefit from it. MSI‐H was associated with reduced perineural invasion and improved OS and DFS. Therefore, this hypothesis warrants further investigation in clinical trials to underscore the prognostic significance of HER‐2 and MSI status and the value of molecular profiling in guiding personalized treatment strategies.